Electrocardiographic and laboratory alterations in anorexic cats - Jessica Junckes; Eduarda Aléxia Nunes Louzada Dias Cavalcanti; Thames Camargo Ignácio; Roberta Oliveira de Carvalho; Guilherme Albuquerque de Oliveira Cavalcanti; Maristela Silveira Palhares (Semina: Ciências Agrárias, 2020)
Anorexia, the result of inadequate nutrient intake, can lead to death and is a constant problem in the feline clinic. However, we did not find any previous studies that evaluated cardiac measures in felines. Therefore, we evaluated 27 emaciated cats by means of hematological exams, urinalysis, and electrocardiography. In the serum, we noted increased creatine kinase, aspartate aminotransferase, and lactate enzyme levels. Further, 62.96% of the cats exhibited electrocardiographic alterations. The most frequent electrocardiographic changes were increased QRS complex duration and QT interval increase. As clinicians become more aware of cardiovascular complications related to malnutrition, they are better able to recognize and assist this animal class.